SALT AND SOVEREIGNTY IN COLONIAL BURMA - LALLY, JAGJEET (The Historical journal, 2021)
Across monsoon Asia, salt is of such vital necessity that controlling its production or supply has historically been connected to the establishment and expression of political authority. On the one hand, rulers maintained the allegiance of their subjects by ensuring their access to salt of suitable price and sufficient quantity. On the other hand, denying rebels their salt was a strategy of conquest and pacification, while the necessity of salt meant it could reliably be taxed to raise state finances. This article first sets out this connection of salt and sovereignty, then examining it in the context of colonial Burma, a province of British India from its annexation until its ‘divorce’ in 1935 (effected in 1937), and thus subject to the Government of India's salt monopoly. Focusing on salt brings into view two aspects of the state (while also permitting analysis of ‘Upper Burma’, which remains rather marginal in the scholarly literature). First, the everyday state and quotidian practices constitutive of its sovereignty, which was negotiated and contested where indigenes were able to exploit the chinks in the state's administrative capacity and its knowledge deficits. Second, in turn, the lumpy topography of state power. The state not only failed to restrict salt production to the extent it desired (with the intention that indigenes would rely on imported salt, whose supply was easier to control and thus tax), but conceded to a highly complex fiscal administration, the variegations in which reflected the uneven distribution in state power – thicker in the delta and thinnest in the uplands.